View of the UPV-CM students on savings - Calisterio, Ma. Coreen; Candolada, Ma. Lira; Solina, Emily; Villan, Rene
Executive summary - This study reflects the view of UPV-CM students toward savings. Specifically, it tells about their concept of savings and the relationship of four major variables that affect or influence their capacity to save, namely : gender, course, amount of allowance, and lifestyles. The respondents of this study are students from UPV-College of Management. Thirty-five are Management majors, thirty-three are enrolled in Marketing, and thirty-two are accountancy students. gender has a close relationship in savings. Female students are more conscious to save than male. This is affected by other factors such as the nature of their course and their lifestyles. Moreover, the amount of allowance of the students determined their capacity to save, since students whose allowance belongs to the top bracket are the ones who have bigger savings.